Civil servants as guardians of virtue or servants of democracy - Smith, Bo; Christensen, Jørgen Grønnegård (Politica, 2016)
West European civil servants see themselves as political bureaucrats, working closely with ministers to prepare and implement governmental policies. These political bureaucrats operate within ministerial cultures emphasizing their ability to accommodate without strict hierarchical commands and controls. Even if these countries basically have upheld a merit civil service, some countries to some extent rely on political appointees. However, there is no indication that this limited politicization influences the quality of governance.